European banking after the 2023 crisis - Thorsten Beck (EconPol Forum, 2024)
The 2023 banking turmoil had limited effects on banks in the euro area and the EU. Nevertheless, there are important lessons to be learned. Business models matter. Specific banks in the US were hit, with a funding structure relying on sectorally concentrated large and related depositors. Bank runs have become faster due to less sticky deposits in an internet-based banking model and social media. Fragility is a feature, not a bug, of banking. There is no simple, one-size-fits-all solution to the prudential regulation of interest rate risk in the banking book. Basel III allows for the implementation of several policy options without major reforms in order to emphasize supervisory intervention, such as the introduction of criteria for risk-based pricing of deposit insurance premiums.
Keywords: 330